Art Music by Caribbean Composers: US Virgin Islands - Gangelhoff, Christine; LeGrand, Cathleen (International Journal of Bahamian Studies, 2011)
Virgin Island music is syncretic, reflecting both African and European heritage. While older traditions including cariso and bamboula are virtually extinct, quelbe is popular throughout the islands, with bands such as Stanley and The Ten Sleepless Nights performing frequently.